The Effect of Social Capital on the Innovation Performance of the Small-Middle Scaled Enterprises of Agribusiness in Bogor Regency - Sugara Mursid; Suharno Suharno; Wahyu Budi Priatna (School of Business, IPB University (SB-IPB), 2018)
The aim of the research was to analyze the relationship between the social capital and innovation performance of agribusiness in Regency Bogor. The sample of the research was set as purposive sampling. There were 38 respondents involved from the nine districts. By the criteria, the entrepreneurs are also the owners of the agribusiness MSMEs and have been running their company for two years minimally. The data were analyzed by Sequal Equation Modeling Partial Least Square (SEM-PLS) method with SMART PLS 3.2.4. Based on the results, the majority of agribusiness MSMEs in Bogor Regency produce local and traditional products and have 1 to 5 employees. They earn money less than 100 million rupiahs annually, and most of them are categorized as the entrepreneurs of the micro and small enterprises. Social norm gives influence on innovation performance significantly, and it is reflected by providing aid to each other, having access to aids and willingness to share any information. The entrepreneurs of the agribusiness MSMEs possessing social norm will increase their innovation performance. Willingness to provide aid is the indicator to contribute significantly to social norm. Social network also gives effects significantly on innovation performance. Social network is reflected by network size, multiplexity and network constraints. The larger the network size, the wider important information related to the enterprises; therefore, it will increase opportunity to innovate. The height of multiplexity and network constraints will reduce the chance to innovate. Multiplexity is the highest indicator contributing to social network whereas trust variable does not give contribution significantly to innovation performance of the agribusiness MSMEs.Keywords: MSMEs, social capital, agribusiness, innovation performance